Early or synchronized gestures facilitate speech recall—a study based on motion capture data - Nirme, Jens; Gulz, Agneta; Haake, Magnus; Gullberg, Marianne (Frontiers in Psychology, 2024)
Temporal coordination between speech and gestures has been thoroughly studied in natural production. In most cases gesture strokes precede or coincide with the stressed syllable in words that they are semantically associated with. Methods. To understand whether processing of speech and gestures is attuned to such temporal coordination, we investigated the effect of delaying, preposing or eliminating individual gestures on the memory for words in an experimental study in which 83 participants watched video sequences of naturalistic 3D-animated speakers generated based on motion capture data. A target word in the sequence appeared a) with a gesture presented in its original position synchronized with speech, b) temporally shifted 500 ms before or c) after the original position, or d) with the gesture eliminated. Participants were asked to retell the videos in a free recall task. The strength of recall was operationalized as the inclusion of the target word in the free recall. Results. Both eliminated and delayed gesture strokes resulted in reduced recall rates compared to synchronized strokes, whereas there was no difference between advanced (preposed) and synchronized strokes. An item-level analysis also showed that the greater the interval between the onsets of delayed strokes and stressed syllables in target words, the greater the negative effect was on recall. Discussion. These results indicate that speech-gesture synchrony affects memory for speech, and that temporal patterns that are common in production lead to the best recall. Importantly, the study also showcases a procedure for using motion capture-based 3D-animated speakers to create an experimental paradigm for the study of speech-gesture comprehension.